Mineral dust and fossil fuel combustion dominate sources of aerosol sulfate in urban Peru identified by sulfur stable isotopes and water-soluble ions. (1st September 2021) - Olson, Elizabeth; Michalski, Greg; Welp, Lisa; Larrea Valdivia, Adrianna E.; Reyes Larico, Juan; Salcedo Peña, Jimena; Fang, Huan; Magara Gomez, Kento; Li, Jianghanyang
Abstract: High sulfur emissions in the Central Andes have in the past been attributed to active volcanoes and numerous copper smelting facilities in the region. This study evaluates the contribution of these sources on Arequipa, Peru through an evaluation of aerosol sulfate δ 34 S values and water-soluble ions (WSI). The anthropogenic and natural sources of particulate pollution were determined by aerosol filter sampling from four different locations (urban, suburban, industrial, and rural) providing a view of the spatial variability of aerosols within the city. Sulfate (avg. 2.97 μm/m 3 ) is the most abundant ion species in the aerosols sampled contributing on average 20% of the molar mass. Ion composition profiles between sampling sites are very similar indicating common sources and high contributions of mobilized local surface salt to the aerosols in this desert region. The regional atmospheric chemistry model (RACM) 0-D run for the area confirms that emissions from fuel combustion sources alone cannot account for the high concentrations of sulfate observed. A combination of the RACM results, WSI data, and a Bayesian δ 34 S isotope mixing model determined that the majority of aerosol sulfates in the area are from mineral dust adding to fossil fuel combustion sources. Mineral dust entrainment in the region is likely elevated by the close proximity of open-pit mining and unpaved roads near the city. Marine organic aerosols and smelting located along the Pacific contribute little to Arequipa's aerosol sulfate concentration. While the influence of volcanic sulfate (9% on average) is low, overall natural sulfate (dust, volcanic, and DMS) accounts for 43% of the aerosol sulfate. Therefore, even though the local environment creates high sulfate background levels, a reduction of sulfate aerosol pollution would be possible if fossil fuel emissions were reduced. Highlights: High sulfate aerosol concentration in southern Peruvian city where sulfate is 20% of PM2.5 aerosol mass. Water-soluble ions and δ 34 S isotopes show high natural background levels of sulfate from desert mineral dust (13–26%). A Bayesian δ 34 S isotope mixing model determined on average 50% of sulfate sourced from oil and coal combustion.